Ghana - 2009 External Review of Public Expenditures and Financial Management : Volume 2. The medium term expenditure framework - World Bank (World Bank, 2012)
The 2009 External Review of Public Expenditures and Financial Management (ERPEFM) is the fifth in a series of annual assessments by some of the development agencies that contribute to the Multi-Donor Budgetary Support (MDBS) in Ghana. The review was prepared in close collaboration and after extensive discussions with senior government officials in the Government of Ghana, in particular with officials from the ministry of finance and economic planning. The main purpose of the review is to inform based on research findings the policy dialogue on public financial management that takes place in Ghana. The implementation of the 2009 budget is happening against the backdrop of the Government's stated objective of reducing the overall fiscal deficit to 9.4 percent of gross domestic product (GDP), down from an estimated 14.5 percent in 2008. The remainder of this chapter is organized as follows. Section B recapitulates the change in Ghanaian public finances in 2008. Section C discusses the country's fiscal outlook and the policy challenges ahead. Section D closes the chapter with the main conclusions and recommendations.